Pengaruh Etos Kerja Islam, Disiplin Kerja, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Badan Pusat Statistik (BPS) Provinsi Bengkulu - Wahyuningsih, Resti Eka; Hak, Nurul; Sumarni, Yenti (Ekonomis: Journal of Economics and Business, 2024)
This examination plans to determine whether the factors of Islamic work ethic, work discipline, work motivation and work environment have an impact on employee performance. The Central Statistics Agency (BPS) of Bengkulu Province was the subject of the research. The population of this study consisted of all employees of the Bengkulu Province Central Statistics Agency, totaling 61 respondents. The data analysis method is multiple linear regression. Based on the test results, the Islamic work ethic and work discipline variables have a partially significant influence on employee performance. For the time being, work motivation and work environment do not have much influence on employee performance. Then simultaneously or together the factors of Islamic work ethic, work discipline, work motivation and work environment essentially influence the implementation of employee performance at the Central Bureau of Statistics (BPS) of Bengkulu Province.